Macrocyclic bis(ureas) as ligands for anion complexation - Kretschmer, Claudia; Dittmann, Gertrud; Beck, Johannes (Beilstein Journal of Organic Chemistry, 2014)
Two macrocyclic bis(ureas) 1 and 2, both based on diphenylurea, have been synthesized. Compound 1 represents the smaller ring with two ethynylene groups as linkers and 2 the larger ring with two butadiynylene groups. On thermal treatment to 130 °C molecule 1 splits up into two dihydroindoloquinolinone (3) molecules. Both compounds 1 and 2 form adducts with polar molecules such as dimethyl sulfoxide (DMSO) and dimethylformamide (DMF) and act as complexing agents towards a series of anions (Cl−, Br−, I−, NO3−, HSO4−). The crystal structures of 3, 2·2DMSO, 2·2DMF, and of the complex NEt4[Br·2] have been determined. Quantitative investigations of the complexation equilibria were performed via 1H NMR titrations. While 1 is a rather weak complexing agent, the large ring of 2 binds anions with association constants up to log K = 7.93 for chloride ions.
Keywords: anion binding; macrocyclic compounds; NMR spectra; supramolecular chemistry; template; urea